2012
DOI: 10.2174/157488612802715663
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Induces Toxicity in Human Neurons Differentiated from Embryonic Stem Cells via Mitochondrial Apoptosis Pathway

Abstract: Ketamine is widely used for anesthesia in pediatric patients. Growing evidence indicates that ketamine causes neurotoxicity in a variety of developing animal models. Our understanding of anesthesia neurotoxicity in humans is currently limited by difficulties in obtaining neurons and performing developmental toxicity studies in fetal and pediatric populations. It may be possible to overcome these challenges by obtaining neurons from human embryonic stem cells (hESCs) in vitro. hESCs are able to replicate indefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 44 publications
6
62
0
Order By: Relevance
“…It is hypothesized that the increase in the NR1 of the NMDA receptor is responsible for apoptosis as the increased expression of the NR1 subunit evokes a raise in Ca 2+ -entry (Slikker et al, 2007;Bosnjak et al, 2012;Liu et al, 2013;Bai et al, 2013). Although [Ca 2+ ] i is necessary for neuronal development, pathologically enhanced Ca 2+ -influx promotes an increase in the [Ca 2+ ] i concentration, results in a rise of reactive oxygen species, increases mitochondrial membrane permeability by members of the bcl-2 family (bcl-2 and BAX) and ultimately, releases cytochrome C (Bosnjak et al, 2012;Bai et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hypothesized that the increase in the NR1 of the NMDA receptor is responsible for apoptosis as the increased expression of the NR1 subunit evokes a raise in Ca 2+ -entry (Slikker et al, 2007;Bosnjak et al, 2012;Liu et al, 2013;Bai et al, 2013). Although [Ca 2+ ] i is necessary for neuronal development, pathologically enhanced Ca 2+ -influx promotes an increase in the [Ca 2+ ] i concentration, results in a rise of reactive oxygen species, increases mitochondrial membrane permeability by members of the bcl-2 family (bcl-2 and BAX) and ultimately, releases cytochrome C (Bosnjak et al, 2012;Bai et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although [Ca 2+ ] i is necessary for neuronal development, pathologically enhanced Ca 2+ -influx promotes an increase in the [Ca 2+ ] i concentration, results in a rise of reactive oxygen species, increases mitochondrial membrane permeability by members of the bcl-2 family (bcl-2 and BAX) and ultimately, releases cytochrome C (Bosnjak et al, 2012;Bai et al, 2013). BAX and bcl-2 are proteins involved in apoptosis, both are localized in the inner mitochondrial membrane.…”
Section: Discussionmentioning
confidence: 99%
“…(H1 cell line, WiCell Research Institute Inc., Madison, WI) were cultured on a feeder layer of mouse embryonic fibroblasts (MEFs) that were mitotically inactivated using mitomycin C (Sigma-Aldrich, St. Louis, MO) as previously described by our laboratory 29,30 . Briefly, culture dishes were coated with 0.1% gelatin overnight in a humidified incubator.…”
Section: Methodsmentioning
confidence: 99%
“…Three hours exposure to ketamine did not produce any signiicant histochemical change, whereas profound brain cell death was observed in the frontal cortex among subjects that were under the efect of ketamine for 9 or 24 hours. In cell culture study of Bosnjak et al [25], they demonstrated that ketamine decreases neuronal viability time and dose dependently, leads to neuronal ultrastructural abnormalities, causes depolarization of mitochondrial membrane potential, induces apoptotic pathway, causes cytochrome c release from mitochondria into cytosol, and induces free oxygen radical production.…”
Section: Intravenous Anestheticsmentioning
confidence: 99%